1954
DOI: 10.1021/ja01642a017
|View full text |Cite
|
Sign up to set email alerts
|

The Depolymerization of Polymethylene and Polyethylene

Abstract: cording to some recent theories of the osmotic second virial coefficient in the limit of large excluded volumes, i.e., for high molecular weight polymer molecules in thermodynamically "good" solvents, the ratio A2M%,/(Rl,)'/* should attain an essentially constant value. Qualitatively the constancy of this ratio is an expression of the expectation that the interactions of polymer molecule pairs in such media resemble collisions of spheres whose volumes are proportional to (7?2W)V2. If, then, the volumes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

1959
1959
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 2 publications
1
87
0
Order By: Relevance
“…Prepared according to the method described by Buckley and Ray [6] by decomposing diazomethane, using trimethyl borate as catalyst. Its molec ules are unbranched without methyl groups, and of high molecular weight [7].…”
Section: Poly (A-methylstyren E) Prepared Thermally By the Dow Chemicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Prepared according to the method described by Buckley and Ray [6] by decomposing diazomethane, using trimethyl borate as catalyst. Its molec ules are unbranched without methyl groups, and of high molecular weight [7].…”
Section: Poly (A-methylstyren E) Prepared Thermally By the Dow Chemicalmentioning
confidence: 99%
“…All these polymers, except number 4, are the same materials as those used previously in work on rates of thermal degradation at higher temperatures in the tungsten spring balance apparatus [1,2,7,8,9]. As in previous work, the samples were heated in a vacuum at 100° C to a constant weight before they were used in the rate experiments.…”
Section: Rate Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to present trends in finding cost-effective energy sources, recent research efforts have focused on the utilization of waste polymeric materials in reacting directly with coal [12,13]. This becomes possible since it is well established that waste plastics undergo depolymerization and degradation above 380˚C by a free radical chain reaction [14]. Although a variety of waste plastics processing methods for obtaining hydrocarbons have been developed in the recent past, there is still a great deal of interest for the mentioned co-liquefaction process due to the fact that coal is an abundant fuel resource [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of waste plastics processing methods for obtaining hydrocarbons have been developed in the recent past, there is still a great deal of interest for the mentioned co-liquefaction process due to the fact that coal is an abundant fuel resource [15]. Hence, this case seems to be quite promising since earlier studies indicated that positive synergism was achieved by processing coal and waste plastics targeting oily yields [14]. This process became achievable due to the fact that waste plastics are characterized by high hydrogen content and molecular structures that are suitable for this transformation [16].…”
Section: Introductionmentioning
confidence: 99%